Identification of the enhancer RNAs related to tumorgenesis of pituitary neuroendocrine tumors - Wang, Liangbo; Wei, Chenlu; Wang, Yu; Huang, Ning; Zhang, Tao; Dai, Yuting; Xue, Li; Lin, Shaojian; Wu, Zhe Bao (Frontiers in Endocrinology, 2023)
Pituitary neuroendocrine tumors (PitNETs), which originate from the pituitary gland, account for 10%–15% of all intracranial neoplasms. Recent studies have indicated that enhancer RNAs (eRNAs) exert regulatory effects on tumor growth. However, the mechanisms underlying the eRNA-mediated tumorigenesis of PitNETs have not been elucidated. In this study, data of 134 PitNETs and 107 normal pituitary samples were retrieved from a public database to identify differentially expressed genes. In total, 1128 differentially expressed eRNAs (DEEs) (four hundred ninety-four upregulated eRNAs and six hundred and thirty-four downregulated eRNAs) were identified. Next, the correlation of DEEs with cancer-related and immune-related gene signatures was examined to establish a co-expression regulatory network comprising 18 DEEs, 50 potential target genes of DEEs, 5 cancer hallmark gene sets, 2 differentially expressed transcription factors, 4 immune cell types, and 4 immune gene sets. Based on this network, the following four therapeutics for PitNETs were identified using Connectivity Map analysis: ciclopirox, bepridil, clomipramine, and alexidine. The growth-inhibitory effects of these therapeutics were validated using in vitro experiments. Ciclopirox exerted potential growth-inhibitory effects on PitNETs. Among the DEEs, GNLY, HOXB7, MRPL33, PRDM16, TCF7, and ZNF26 were determined to be potential diagnostic and therapeutic biomarkers for PitNETs. This study demonstrated the roles of eRNAs in the occurrence and development of PitNETs and revealed that ciclopirox was a potential therapeutic for pituitary adenomas.